2015
DOI: 10.1371/journal.pone.0138436
|View full text |Cite
|
Sign up to set email alerts
|

glpx Gene in Mycobacterium tuberculosis Is Required for In Vitro Gluconeogenic Growth and In Vivo Survival

Abstract: Several enzymes involved in central carbon metabolism and gluconeogenesisplay a critical role in survival and pathogenesis of Mycobacterium tuberculosis (Mtb). The only known functional fructose 1,6-bisphosphatase (FBPase) in Mtb is encoded by the glpX gene and belongs to the Class II sub-family of FBPase. We describe herein the generation of a ΔglpX strain using homologous recombination. Although the growth profile of ΔglpX is comparable to that of wild type Mtb when grown on the standard enrichment media, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Phosphoenolpyruvate carboxykinase (PEPCK) catalyzes the first committed step of gluconeogenesis and has been shown to be important for Mtb growth during active and latent stages of the disease (Marrero et al, 2010). In addition, three enzymes involved in glycerol metabolism have also been considered as possible targets: triosephosphate isomerase (TPI; Trujillo et al, 2014), fructose bisphosphate aldolase (FBA; Puckett et al, 2014) and fructose-1,6-bisphosphatase (FBPase; Gutka et al, 2015). Mtb fructose-1,6-bisphosphatase (MtFBPaseII), the enzyme encoded by the glpX gene, is the third component of the glpFKX operon involved in the growth of Mtb using glycerol as the sole carbon source (Donahue et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphoenolpyruvate carboxykinase (PEPCK) catalyzes the first committed step of gluconeogenesis and has been shown to be important for Mtb growth during active and latent stages of the disease (Marrero et al, 2010). In addition, three enzymes involved in glycerol metabolism have also been considered as possible targets: triosephosphate isomerase (TPI; Trujillo et al, 2014), fructose bisphosphate aldolase (FBA; Puckett et al, 2014) and fructose-1,6-bisphosphatase (FBPase; Gutka et al, 2015). Mtb fructose-1,6-bisphosphatase (MtFBPaseII), the enzyme encoded by the glpX gene, is the third component of the glpFKX operon involved in the growth of Mtb using glycerol as the sole carbon source (Donahue et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent studies using genetic knockout and complementation protocols have shown that gluconeogenesis and the bisphosphatase activity of MtFBPaseII are essential for virulence in Mtb grown using glycerol as an alternative carbon source (Gutka et al, 2015;Ganapathy et al, 2015). In addition, extended (180 d) monitoring of the survival profile of mice infected with ÁglpX mutant Mtb showed that the gene is essential for growth in the acute phase and for long-term survival during the chronic phase of Mtb infection (Gutka et al, 2015). The FBPase encoded by the glpX gene has also been validated as an essential target in the closely related species M. marinum (Tong et al, 2016) and in the important bacterial pathogen Francisella tularensis (Brissac et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These results thus implicated gluconeogenesis as a key physiologic determinant of pckA’s essentiality. This importance was confirmed, amongst others, by Ganapathy et al , who showed the essentiality of fructose bisphosphatase (FBPase), a dedicated gluconeogenic enzyme that catalyzes the unidirectional conversion of fructose 1,6-bisphosphate to fructose 6-phosphate [36,37]. Although Mtb was annotated to encode a single FBPase ( glpX ), a combined genetic and metabolomics approach revealed a second FBPase activity ( gpm2 ) capable of supporting gluconeogenesis in the absence of glpX , leaving GlpX a poor drug target [36].…”
Section: Target-based Drug Developmentmentioning
confidence: 81%
“…Two recent studies confirmed the important roles of FBPase encoding genes in gluconeogenesis and pathogenesis of Mtb , and concluded that glpX encodes an FBPase, yet the FBPase activity was not entirely eliminated in Δ glpX [ 18 ]. The gene glpX was demonstrated essential for proliferation and virulence of Mtb [ 18 ], and another gene gpm2 (Rv3214) was identified to encode a novel functional FBPase [ 19 ]. Notably, MMAR_1343 which is annotated as a homologous gene to Rv3214 in M .…”
Section: Discussionmentioning
confidence: 99%
“…An earlier report demonstrated that the overexpression of Mtb glpX rescued the growth defects of an Escherichia coli FBPase mutant [ 17 ]. In a recent report, glpX was demonstrated essential for both proliferation and virulence of Mtb [ 18 ]. In addition, gene gpm2 (Rv3214) was identified as a novel FBPase [ 19 ], and the gluconeogenesis and virulence were seriously affected by the disruption of both gpm2 and glpX .…”
Section: Introductionmentioning
confidence: 99%